2002
DOI: 10.1530/eje.0.1460163
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of reduced in vivo surface expression of activating mutant thyrotrophin receptors in thyroid sections

Abstract: Objective: Thyroid function and growth are controlled by TSH. Hyperthyroidism can be due to Graves' Disease (GD), in which thyroid-stimulating antibodies mimic TSH, or gain-of-function mutations in the TSH receptor (TSHR). These activating mutations have poor surface expression when assessed in non-thyroidal cells in vitro but nothing is known of their in vivo behaviour. Several TSHR antibodies have been produced but none has been applied to thyroid paraffin sections. This study aimed to develop a technique su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Furthermore, the results we obtained from preadipocytes in culture showing increased TSHR transcripts (the current study) and TSHR immunoreactivity (Crisp et al 2000) imply that transcript also correlates with protein in cultured primary cells. The higher levels of TSHR transcript in GD thyroid tissue compared with MNG mirrors our previous demonstration of receptor protein in these glands using ICC (Sequeira et al 2002).…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, the results we obtained from preadipocytes in culture showing increased TSHR transcripts (the current study) and TSHR immunoreactivity (Crisp et al 2000) imply that transcript also correlates with protein in cultured primary cells. The higher levels of TSHR transcript in GD thyroid tissue compared with MNG mirrors our previous demonstration of receptor protein in these glands using ICC (Sequeira et al 2002).…”
Section: Discussionsupporting
confidence: 85%
“…cAMP and inositol phosphate production, for the mutants in comparison with the WT TSHR (3,4,6,11). This system, however, cannot be relied upon to generate data representative of effects in normal human thyroid cells because 1) it involves gross artefactual overexpression of the receptors, whereas expression of native TSHR in thyroid follicular cells, and particularly mutant forms, is remarkably low (12,13); 2) signaling in COS-7 cells may not accurately reflect the situation in thyroid follicular cells due to the specificity of cell signaling (14); and 3) investigation of direct biological effects on growth, differentiation, and function is not possible in a cell system, in which gene expression is only transient.…”
mentioning
confidence: 99%
“…Comparison of the specific constitutive activity index (basal cAMP/receptor number) showed that the activities of Asp619Gly and Ala623Val TSHRs in the third intracellular loop were approximately one sixth of those of Thr632Ile and Cys672Tyr TSHRs in TM6 and TM7, respectively [35]. The constitutively activating TSHR mutations generally exhibit reduced surface expression as compared with wt TSHR, because of interference with correct folding and trafficking of the receptor to the plasma membrane [36]. Because the expression levels and basal cAMP levels of Asp619Gly TSHR are almost equivalent between stably transfected CHO cells and transiently transfected COS-7 cells [30], it seems that Asp617Tyr TSHR is a relatively weak stimulator of cAMP production.…”
Section: Discussionmentioning
confidence: 99%